Job Satisfaction and Turnover Intention of Nurses in Public Hospitals in Northern Negros Occidental - Sentinar, Amelyn A.; Arnibal, Sheila P. (Philippine Social Science Journal, 2025)
Addressing the critical shortage of nurses in Philippine public hospitals, this study examines the relationship between job satisfaction and turnover intentions among 103 nurses in Northern Negros Occidental. Using a quantitative descriptive-correlational design, the research reveals a strong inverse relationship between the two variables: while nurses generally reported high job satisfaction, turnover intentions remained moderate, particularly among older, male, and married individuals. The findings identify civil status as a key demographic factor and underscore the need for healthcare organizations to implement evidence-based retention strategies, such as mentorship and stress-reduction programs. To further understand these dynamics, future research should explore qualitative factors like workplace culture and employ longitudinal designs to track causality over time.